The Mind and Heart of the Social Child: Developing the Empathy and Theory of Mind Scale. (10th November 2015) - Wang, Zhenlin; Wang, Lamei
Abstract : Empathy and theory of mind (ToM) are distinctive psychological constructs in predicting children's social functioning. This study provided evidence of the independent nature of these constructs and developed a parent questionnaire for measuring individual differences in children's empathy and ToM. In Study 1, exploratory factor analysis and confirmatory factor analysis based on responses of 116 parents of Hong Kong children established a three-factor structure of the Empathy and Theory of Mind Scale (EToMS), that is, Empathy, Nice ToM, and Nasty ToM. An additional 189 parents of Study 2 confirmed this three-factor model. A subsample of 93 children (M = 4.97, SD = .84, 47 boys) from Study 2 took part in child measures of helping and lying behaviors as well as false belief understanding. The results supported the reliability and validity of the EToMS, making it a useful assessment of children's social predispositions.